2017
DOI: 10.7155/jgaa.00443
|View full text |Cite
|
Sign up to set email alerts
|

Block Crossings in Storyline Visualizations

Abstract: Abstract. Storyline visualizations help visualize encounters of the characters in a story over time. Each character is represented by an xmonotone curve that goes from left to right. A meeting is represented by having the characters that participate in the meeting run close together for some time. In order to keep the visual complexity low, rather than just minimizing pairwise crossings of curves, we propose to count block crossings, that is, pairs of intersecting bundles of lines. Our main results are as foll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 10 publications
(16 reference statements)
0
20
0
Order By: Relevance
“…In an earlier paper [3], we introduced the concept of minimizing block crossings for drawing storylines. We showed that block crossing minimization in storylines is NP-hard.…”
Section: Concurrentmentioning
confidence: 99%
See 3 more Smart Citations
“…In an earlier paper [3], we introduced the concept of minimizing block crossings for drawing storylines. We showed that block crossing minimization in storylines is NP-hard.…”
Section: Concurrentmentioning
confidence: 99%
“…(This more general problem is clearly NP-hard as well.) Secondly, we have now implemented the exact algorithms of our earlier paper [3], which enables an experimental evaluation and comparison. We see that the new algorithm is able to handle larger realistic instances than our previous algorithms, but that the FPT algorithm also has practical relevance.…”
Section: Concurrentmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the practical effectiveness of this approach, it has quickly been adopted by the InfoVis community [7,13,15,16,22]. However, bundled drawings have only recently attracted study from a theoretical point of view [1,9,11,12].…”
Section: Introductionmentioning
confidence: 99%